Analisis Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi di Indonesia Tahun 2020–2024 - Dian Sari Br Sitepu; Irsad Lubis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the determinants of Indonesia’s economic growth during the period 2020–2024, focusing on Foreign Direct Investment (FDI) and Domestic Investment (DI). Using annual macroeconomic data from BPS and BKPM, the study adopts a quantitative approach with multiple regression to examine how investment inflows contribute to national economic performance. The findings show that both FDI and DI have significant roles in encouraging economic growth, although the magnitude of their effects varies across years due to global shocks, including the COVID-19 pandemic and post-pandemic recovery. The study highlights the need for consistent investment policies to accelerate sustainable economic growth.